Atypical manifestations of visceral leishmaniasis in patients with HIV in north Ethiopia: a gap in guidelines for the management of opportunistic infections in resource poor settings. Issue 1 (January 2015) - Diro, Ermias; van Griensven, Johan; Mohammed, Rezika; Colebunders, Robert; Asefa, Mesfin; Hailu, Asrat; Lynen, Lutgarde
Summary In regions where it is endemic, visceral leishmaniasis is an important opportunistic infectious disease in people living with HIV. Typically, clinical presentation of visceral leishmaniasis includes chronic fever, hepatosplenomegaly, and weight loss. In Leishmania infantum endemic regions in Europe, atypical visceral leishmaniasis presentations have been well documented, with almost every possible organ involved. However, such reports are rare in Leishmania donovani endemic regions such as east Africa. In this Personal View, we describe the various atypical disease presentations in patients screened as part of an HIV and visceral leishmaniasis clinical trial in north Ethiopia, where up to 40% of patients with visceral leishmaniasis are co-infected with HIV. Atypical presentations such as these are not covered in clinical guidelines used in these settings. Apart from the lack of diagnostic facilities, this gap contributes to the underdiagnosis of atypical visceral leishmaniasis, with associated morbidity and mortality. Involvement of clinicians experienced with the management of HIV and visceral leishmaniasis co-infection in the development of HIV clinical guidelines in affected regions is warranted.